Physical activity, mental health, support networks, lifestyle, and memory in older adults during the COVID-19 pandemic - Ana Luisa Lino-González; Bernarda Téllez-Alanís; Paul Carrillo-Mora; Bruma Palacios-Hernández; Adela Hernández-Galván; Alfredo Durand-Rivera (Neurology Perspectives, 2024)
Introduction: At the beginning of the pandemic, it was suggested that lockdown and social distancing could affect the physical, emotional, and cognitive aspects of people, especially the elderly. Objective: To determine the characteristics of physical activity, mental health, support networks, and lifestyle of the elderly in lockdown by COVID-19 and its relationship with memory functioning. Method: 100 healthy elderlies (age ≥60 years) participated and answered a set of online instruments that evaluated 6 variables: demographic data, physical activity, mental health, social support networks, lifestyle, and subjective memory. MoCA and Neuropsi tests were applied through a video call. The study was conducted between September 2021 and May 2022. Results: Participants reported being and having been physically active, the presence of trait and state anxiety was found in 100%, also a higher perception of support from the family network. Insomnia was found in 46% of the sample, increased consumption of stimulant beverages and tobacco, and adequate competence in handling information and communication media. The memory functioning of 97% of the participants was normal or high normal, with fair self-perception of memory functioning. Correlations were moderate between mental health and self-perceived memory. Conclusions: The results suggest that having social support networks, good mental health, and staying physically and cognitively active favour memory function. Resumen: Introducción: Al inicio de la pandemia se planteó que el confinamiento y el distanciamiento físico y social pudieran afectar aspectos físicos, emocionales y cognitivos de las personas, en especial de los adultos mayores (AM). Objetivo: Determinar las características de la actividad física, la salud mental, las redes de apoyo y el estilo de vida de AM en el confinamiento por COVID-19 y su relación con el funcionamiento de la memoria. Método: Participaron 100 AM saludables (edad ≥60 años) quienes contestaron un conjunto de instrumentos en línea que evaluaron seis variables: datos demográficos, actividad física, salud mental, redes de apoyo social, estilo de vida y memoria subjetiva. Mediante una videollamada se aplicó el MoCA y el Neuropsi. El estudio se realizó entre septiembre 2021-mayo 2022. Resultados: Los participantes refieren ser y haber sido activos físicamente, se encontró presencia de ansiedad rasgo y estado en el 100%, mayor percepción de porcentaje de apoyo de la red familiar. Se encontró insomnio en el 46% de la muestra, incremento en el consumo de bebidas estimulantes y tabaco, y competencia adecuada en el manejo de medios informativos y comunicativos. El funcionamiento de la memoria del 97% de los participantes fue normal o normal alto, con una autopercepción regular del funcionamiento de la memoria. Las correlaciones fueron moderadas entre salud mental y memoria autopercibida. Conclusiones: Los resultados sugieren que contar con redes de apoyo social, una buena salud mental y mantenerse activos física y cognitivamente, favorece el funcionamiento de la memoria.